If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 = 9x + 10 Reorder the terms: 2 + 6x = 9x + 10 Reorder the terms: 2 + 6x = 10 + 9x Solving 2 + 6x = 10 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 2 + 6x + -9x = 10 + 9x + -9x Combine like terms: 6x + -9x = -3x 2 + -3x = 10 + 9x + -9x Combine like terms: 9x + -9x = 0 2 + -3x = 10 + 0 2 + -3x = 10 Add '-2' to each side of the equation. 2 + -2 + -3x = 10 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 10 + -2 -3x = 10 + -2 Combine like terms: 10 + -2 = 8 -3x = 8 Divide each side by '-3'. x = -2.666666667 Simplifying x = -2.666666667
| 5.4=-6.1+t | | 3(n-18)=2n+1 | | 10(x-1)=4x+26 | | 180=(3x+8) | | -4.4j-2=-5.5j-4.2 | | 4r+2+5r-12=125 | | 3a+4=18+a | | 1.9m-6.2=-14.6+4.7m | | 4(0)-3y=0 | | 6x-12=8x-16 | | =x+6y | | (g+4)-3a=1+g | | 6x+11=2x+5 | | -x+5=4x+71 | | 3(-2-5)+11= | | 3x+6=3x+22 | | 56-5x=13x+24 | | p-5(2-3)+1= | | .75(4x+8)=-12 | | 4x-3(0)=0 | | 5(3-2k)=8(3k-4)-4(1+7k) | | 4x+-2=3x+4 | | 3(2-X)+8=2(X-4)+6 | | y=3x^4-12x^3-24x^2-7 | | 2(x+4)=2(x-4)+4x | | .40x-9=7-.60x | | 3(3+2m)+3m=-9 | | x+-3=21 | | 118-2x=6x+21 | | -.08=g+.07 | | 6-6m=3(x+7m) | | 2y=x+2 |